Transcriptome Analysis of Effects of Folic Acid Supplement on Gene Expression in Liver of Broiler Chickens - Zhang, Yujie; Zhang, Ningbo; Liu, Lin; Wang, Yan; Xing, Jinyi; Li, Xiuling (Frontiers in Veterinary Science, 2021)
Folic acid is a water-soluble B vitamin, and plays an important role in regulating gene expression and methylation. The liver is the major site of lipid biosynthesis in the chicken. Nevertheless, how gene expression and regulatory networks are affected by folic acid in liver of broilers are poorly understood. This paper conducted the RNA-seq technology on the liver of broilers under folic acid challenge investigation. First, 405 differentially expressed genes (DEGs), including 157 significantly upregulated and 248 downregulated, were detected between the control group (C) and the 5 mg folic acid group (M). Second, 68 upregulated DEGs and 142 downregulated DEGs were determined between C group and 10 mg folic acid group (H). Third, there were 165 upregulated genes and 179 downregulated genes between M and H groups. Of these DEGs, 903 DEGs were successfully annotated in the public databases. The functional classification based on GO and KEEGG showed that “general function prediction only” represented the largest functional classes, “cell cycle” (C vs. M; M vs. H), and “neuroactive ligand-receptor interaction” (C vs. H) were the highest unique sequences among three groups. SNP analysis indicated that numbers of C, M and H groups were 145,450, 146,131, and 123,004, respectively. Total new predicted alternative splicing events in C, M, and H groups were 9,521, 9,328, and 8,929, respectively. A protein-protein interaction (PPI) network was constructed, and the top 10 hub genes were evaluated among three groups. The results of real time PCR indicated that mRNA abundance of PPARγ and FAS in abdominal fat of M and H groups were reduced compared with the C group (P < 0.05). Ultramicroscopy results showed that folic acid could reduce lipid droplets in livers from chickens. Finally, contents of LPL, PPARγ, and FAS in abdominal fat were decreased with the folic acid supplmented diets (P < 0.01). These findings reveal the effects of folic acid supplemention on gene expression in liver of broilers, which can provide information for understanding the molecular mechanisms of folic acid regulating liver lipid metabolism.